(untitled) (Bridging Cultures, 2021)
This paper focuses on a particular category of verbs known as multi-word verbs, verb combinations or group verbs, which category constitutes a key element of the English lexicon and is characterized by considerable dissensus among linguists. In order to shed some light on this topic, this work examines the concept of multi-word verbs, their main features, and the different subcategories they comprise, adopting a semantic and syntactic approach. For such end, it alludes to the most significant characteristics of each subcategory and provides examples thereof. Furthermore, it points out some of the problems that the lack of recognition of these verbs may pose for the understanding of texts.